MEMBANGUN SISTEM PENDIDIKAN MULTIKULTURAL DI INDONESIA - Natalis Sukma Permana (Lembaga Penelitian STKIP Widya Yuwana, 2018)
Education is one of the elements of character building and human self-development. Education is expected to provide learning so that learners are able to understand themselves, others, the community environment and all the differences that exist in the environment and be tolerant to all the differences that exist in society. Multicultural education is expected to be one of the ways in which learners develop tolerant attitudes toward different racial, ethnic, social and cultural groups, religions, etc. According to UU No. 20 Year 2003 about the National Education System mentions